PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 023 SEDINGINAN KECAMATAN TANAH PUTIH - Rusmidar '; Otang Kurniaman; Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the low learning outcomes IPA Elementary School fifth grade students Sedinginan 023, as seen from the average value of students is 59.75. Of the 20 students who achieve above KKM only 8 people (40%), while that has not reached KKM 12 people (60%), KKM predetermined value is 70. The problem of this study